Transforming Qur’anic Literacy among Inmates through a Semi-Pesantren Model in Lembaga Pemasyarakatan Bitung - Akil, Muhammad; Subeitan, Syahrul Mubarak (Institut Agama Islam Negeri (IAIN) Manado, 2025)
This study examines how a semi-pesantren (Islamic Boarding School) educational model shapes Qur’anic literacy among inmates at Lembaga Pemasyarakatan Bitung, Indonesia. While studies on prison religious education are growing, limited research explains how Qur’anic literacy is developed pedagogically in correctional settings and how it relates to rehabilitation in practice. Using qualitative field research with a descriptive-analytical approach, data were collected through in-depth interviews, participant observation, and documentation, and then analyzed thematically. In this study, Qur’anic literacy refers to foundational competencies in recognizing hija’iyyah letters, reading Qur’anic text, and participating in guided religious learning. The findings show that the semi-pesantren model combines tafriq and taushil methods for letter recognition and reading development with structured learning in taḥfīẓ, fiqh, ‘aqidah, Islamic history, and basic Arabic. This integrated model supports the gradual development of Qur’anic reading and writing skills while also encouraging religious discipline, moral reflection, and constructive behavioral change within the prison environment. The article’s theoretical contribution lies in proposing a context-based framework that links Qur’anic literacy formation to faith-based rehabilitation through an adaptive semi-pesantren model in correctional institutions.